‘Die hand aan die wieg regeer die land [The hand that rocks the cradle rules the land]’: Exploring the Agency and Identity of Women in the Ossewa- Brandwag, 1939–1954 - Blignaut, Charl (Unisa Press, 2015)
The Ossewa-Brandwag (Oxwagon Sentinal) was an Afrikaner nationalist organisation strongly influenced by the dominant Fascist ideologies between the two world wars. Within a few years the organization became a mass movement with more than a hundred thousand members. This also included tens of thousands of women. This article sets out to show how members of the Ossewa-Brandwag Vroue-afdeling (Women's Department) were active social agents who played an indispensable part in running the movement. It further assesses how OB women articulated and interpreted their female identity as volksmoeders. A special emphasis is placed on women's role as fundraisers as well as their discursive construction of Afrikaner femininity. This evaluation is done against the backdrop of the OB's 'ideal image of womanhood' which normatively dictated femininity. As such this article builds upon the research already done on the volksmoeder in order to shed light on the agency of a certain group of people who have received little historical attention in the past. Through assessing the nature of OB women's fundraising it becomes evident that it would have been impossible for the movement to exist without its female members. Furthermore their own articulation of the conventional ideal of Afrikaner womanhood shows that women construed the volksmoeder as a potent tool of maternalist power.
Keywords: Women; gender; women’s history; gender history; Afrikaner women; Afrikaner nationalism; fundraising; Ossewa-Brandwag; volksmoeder (mother of the nation)